Characterization, extraction optimization and microencapsulation of bioactive compounds from the cellulase-treated MD2 pineapple [Ananas comosus L. (Merr)] peel - Nordin, Nur Liyana (2024)
Pineapple waste are often discarded during processing and fresh consumption. Often, these waste would accumulate and decompose in landfills. The biodecomposition of pineapple wastes led to the release of methane gas which causes global warming. Alternatively, pineapple waste could be utilized as a functional Halal ingredient to overcome disposal issues. Thus, this study aimed to develop a powder ingredient from the enzymetreated MD2 pineapple peel extract as a Halal component following the specific objectives; 1) to characterize the phenolic and volatile compounds from MD2 pineapple peel and core extracts, 2) to study the effect of pectinase and cellulase in the extraction of phenolics and volatile compounds from MD2 pineapple peel extracts, 3) to study the extraction process parameters by optimization using response surface methodology (RSM) on MD2 pineapple peel extracts 4) to study the effect of carrier agents and drying techniques in the encapsulation of extracts on its functional properties. Enzyme treatments were performed on MD2 pineapple peel under the influence of different enzyme concentrations (0-1.5% (v/v), and solid to solvent ratios (1:1-1:8 g/mL). In order to identify the kinetic parameters, second-order kinetic modelling was evaluated. Then, the identification of different phenolic fractions was carried out using acid-alkali hydrolysis. To further optimize, response surface methodology was employed to evaluate the optimal conditions of the extraction process. The optimized cellulase-treated MD2 pineapple peel extract was encapsulated by both spray-drying and foam-mat drying. Bioactive volatile compounds were identified in the extracts and microencapsulated cellulase-treated MD2 pineapple peel extract powder. The MD2 pineapple peel extracts were observed to show substantially greater (p<0.05) amounts of total phenolic (TPC) and flavonoid (TFC) compounds than the core extract. Furthermore, peel extract showed improved antioxidant activity, with an IC50 of 0.63 mg/mL in comparison to the core. Meanwhile, bioactive volatile compounds identified were 5-(Hydroxymethyl) furan-2-carbaldehyde (aldehyde), 4H-Pyran-4-one, 2, 3-dihydro-3, 5-dihydroxy-6-methyl (DDMP), 1,2-benzenediol, 1,4-benzenediol, n-decanoic and n-Hezadecanoic acids. The effect of enzyme-assisted extraction on phenolics showed that the extraction process improved at a treatment of 1.5% (v/v) cellulase concentration, and 1:4 g/mL of solid to solvent ratio, respectively. The maximum yield of phenolics obtained by cellulase extraction was 8.72 mg GAE/g per dry weight basis (DW) using second-order kinetic modelling (R2 = 0.9189). When compared to nonenzyme treatment, insoluble-bound phenolics (IBP) extraction increased considerably (p<0.05) by 99.79% following the cellulase treatment. Bioactive volatile compounds present comprised of benzophenone, beta-sitosterol, gamma-sitosterol, stigmast-8(14)-en-3 beta.ol and phenol, 2, 4-bis (1,1- dimethyl ethyl). Through optimisation of cellulase-assisted extraction process using RSM, parameter conditions obtained were 48.21°C and 132 min of extraction temperature and time, respectively. Meanwhile, during the encapsulation process, spray-drying showed good physical properties. Both drying techniques showed good encapsulation efficiency (EE%) of above 89% with spray-drying showing the highest solubility (75.42 – 98.53%). Encapsulation of IBP and bioactive volatile compounds using 10% GA comprised of 2-Methoxy-4-vinylphenol and Phenol, 2,4-bis(1,1-dimethylethyl). In conclusion, an improved extraction process utilizing cellulase and optimization enhanced the release of phenolics from MD2 pineapple peel extracts. Alternatively, the presence of esters and aldehydes detected in the extracts and microencapsulated powder could replace synthetic flavouring agents such as vanillin extracted using alcohol. Meanwhile, the presence of fatty acids and sterols could replace fatty acids derived from pork fat. Furthermore, microencapsulated cellulase-treated MD2 pineapple peel extract powder rich in insoluble-bound phenolics, and bioactive volatile compounds may find applications as ingredients in Halal additives, pharmaceutical and cosmetic products.